A comparison of monetary policy rules in a HANK model - Michael Dobrew; Rafael Gerke; Sebastian Giesen; Joost Röttger (Deutsche Bundesbank, 2021)
This paper provides a comparison of monetary policy rules with make-up and/or asymmetric elements for a heterogeneous agent New Keynesian (HANK) model. The model features incomplete financial markets, nominal price and wage rigidities, rational expectations, an occasionally binding effective lower bound (ELB) on the short-term nominal interest rate as well as aggregate demand and cost-push shocks. Simulations show that symmetric policy rules with make-up elements can substantially lower the downward inflation bias induced by the ELB and reduce macroeconomic volatility. Asymmetric policy rules can address the downward inflation bias as well but lead to a substantial overshooting of the inflation target if they also feature make-up elements. The predictions of the HANK model for the considered policy rules are close to those obtained for a corresponding (representative agent) model version with complete markets.
Keywords: D31; E21; E31; E52; E58; J31; 330; Monetary Policy; HANK; Household Heterogeneity; Effective Lower Bound; Make-Up Strategies; Asymmetric Policy Rules; Inequality